Autism Spectrum Disorder Risk Factor Met Regulates the Organization of Inhibitory Synapses - Jeckel, Pauline; Kriebel, Martin; Volkmer, Hansjürgen (Frontiers in Molecular Neuroscience, 2021)
A common hypothesis explains autism spectrum disorder as a neurodevelopmental disorder linked to excitatory/inhibitory imbalance in neuronal network connectivity. Mutation of genes including Met and downstream signaling components, e.g. PTEN, Tsc2 and Rheb are involved in the control of synapse formation and stabilization and were all considered as risk genes for autism spectrum disorder. While the impact of Met on glutamatergic synapses was widely appreciated, its contribution to the stability of inhibitory, GABAergic synapses is poorly understood. Stabilization of GABAergic synapses depends on clustering of the postsynaptic scaffolding protein gephyrin. Here, we show in vivo and in vitro that Met is necessary and sufficient for the stabilization of GABAergic synapses via induction of gephyrin clustering. Likewise, we provide evidence for Met-dependent gephyrin clustering via activation of mTOR. Our results support the notion that deficient GABAergic signaling represents a pathomechanism for autism spectrum disorder.